ANTA GRANDE DO ZAMBUJEIRO (ÉVORA, PORTUGAL): CONTRIBUTO PARA O CONHECIMENTO DAS CERÂMICAS - Rocha, Leonor (2015)
Of the hundreds of funerary megalithic monuments registered in Alentejo, of different sizes and types, one stands out by its monumentality: the Anta Grande do Zambujeiro. In recent years we have undertaken a project to study the archaeological materials (with exception of schist plates) this megalithic funerary monuments identified in the sixties of the 20th century, by Henry Leonor Pina. The various interventions in this monument, by different investigators, eventually ever being fully published getting the spoils deposited in the Museum of Évora. Wanted of this work was to present a summary of existing ceramic although part of the collection is not yet in a position to be treated.